Immune-Response of Individuals after Immunization with Rubella Vaccine: Ghanima Sadik M ,Layla Fouad Ali - Ali, Layla Fouad (The Iraqi Journal of Veterinary Medicine, 2011)
In this study 72 blood samples were collected from healthy individuals. Thirty blood samples were taken from children with age range (12-18) and twenty blood samples from females with age range (12-15) years old 2-4 after two weeks of vaccination with rubella vaccine. Control group included 12 healthy children and 10 healthy females both did not have rubella vaccine through their life. These samples were tested to evaluate the immune-status of individuals after immunization. In this study specific haemagglutination antibodies and IgM antibodies were measured and total Immunoglobulines (IgM, IgG and IgA) also determined. Lymphocyte transformation and ability of phagocyte cell to phagocytosis were measured. The results showed decrease in total IgG and IgA with an increase in the level IgM in children and females with significant differences (P<0.01), in comparing with control groups. An increase in the percentage of phagocytic activity of phagocyte cells in both groups (children and females) with a significant differences (P<0.05) in comparing with control group. Non significant differences in humeral and cellular immune Response between children and female groups.